Implementasi Teori Konstruktivistik Dalam Proses Pembelajaran Pendidikan Agama Islam - Yova Atika; Reka Amelia Lestari (Pusat Riset dan Inovasi Nasional, 2023)
This research is motivated by the important role of students in building constructive habits of mind. In order for students to have the habit of thinking, teachers need freedom and a learning attitude to achieve this through constructivist theory-based learning. This research is field research (Field Research) which is descriptive qualitative in nature. The subjects of this research are Islamic Religious Education teachers. So this research uses purposive sampling. Purposive sampling is a person who is considered capable of providing information to make it easier for the writer to obtain information from the object under study. Data collection techniques use observation and interviews. The results of this research concluded that the steps in implementing constructivist learning theory at SDUA Taman Harapan Curup are: a. introduction, namely by making preparations, by looking at the material to be taught, b. In essence, the teacher instructs students to form small groups, one group consisting of two people, and the teacher gives assignments to students to discuss and analyze the problems given. c. Closing activity, the teacher instructs students to present the results of their discussion.